Design and Implementation of Enhanced Surveillance Platform with Low-Power Wireless Audio Sensor Network - Guotao Zhao; Huadong Ma; Yan Sun; Hong Luo (International Journal of Distributed Sensor Networks)
Video surveillance system, which can provide real-time display of the monitored scene and video playback, has been employed in many areas including commercial security, accident investigation, law enforcement, and emergency response. However, audio which carries important information not available in video is usually not taken seriously and used effectively. In this paper, we develop an enhanced surveillance platform by organically integrating the low-power wireless audio sensor network (WASN) with the traditional visual surveillance network. We can obtain more comprehensive and precise monitoring without the limitation of the line-of-sight and lighting condition. Moreover, this platform is designed and built for providing key support to varieties of applications in wireless multimedia sensor networks. This paper describes the platform architecture, including design, implementation, and performance. We describe the hardware and software components of the audio/video sensors. Then, we present the multimedia synchronization mechanism in the heterogeneous network which is the foundation of applications in the proposed platform. Besides, we describe a sample application and data management mechanism that we have implemented to show the usefulness of our platform. Our experiments include an in-depth analysis of the bottlenecks within the platform as well as measurements for the various components.